Impact on the display of power cheerleading ability of university students I-II levels of accreditation - Kryvoruchko N.V; Masljak I.P; Zhuravlyova I.N (Kharkov National Pedagogical University, 2013)
Reflects the dynamics of indicators of the level of development of power abilities of students under the influence of specially selected exercises cheerleading. The study involved 385 students (age 15-17 years). The level of the forces will determine by tests: flexion-extension hand-ups, lifting the torso in the saddle for 1 minute, jumping on one leg with the progress, carpal dynamometry. Revealed low levels of manifestation of the power in the first stage. Most significantly improved the results of flexion-extension hand-ups (I course to 32,28%, II course at 21,77%, III course for 25.60%;). According to the results of the lifting body in the saddle improved results of 12.41%, 10.80%, 11.98%, respectively. According to the results of the hops on one foot with the progress - by 5.78%, 4.70%, 4.97%, respectively. According to the wrist of the dynamometer, at 6.31%, 5.36%, 5.89% respectively. The most significant growth results have been observed mainly at students aged 15 years.